2015
DOI: 10.3390/chromatography2030545
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Smectite Colloids: Characterization of Nanoparticles after Co-Precipitation in the Presence of Lanthanides and Tetravalent Elements (Zr, Th)

Abstract: The magnesian smectite hectorite is a corrosion product frequently detected in nuclear waste glass alteration experiments. The structural incorporation of a single trivalent lanthanide was previously demonstrated. Hectorite was presently synthesized, for the first time, in the presence of several lanthanides (La, Eu, Yb) following a multi-step synthesis protocol. The smallest-sized particles (nanoparticles, NPs) were isolated by centrifugation and analyzed by asymmetrical flow field-flow fractionation (AsFlFFF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 67 publications
(73 reference statements)
2
6
0
Order By: Relevance
“…The hectorite octahedral sheet mostly contains Mg which can be used as an indicator of the pres ence of the smectite. Information on the Y(III) binding mode with the smectite can be derived from the variation of the Mg:Y ratio as a func tion of the size (Bouby et al, 2011(Bouby et al, , 2012(Bouby et al, , 2015Finck et al, 2012). For Y structurally incorporated within the hectorite structure, the Mg:Y ratio is expected to be constant for all particle sizes.…”
Section: Asymmetrical Flow Field Flow Fractionation (Asflfff)mentioning
confidence: 99%
See 2 more Smart Citations
“…The hectorite octahedral sheet mostly contains Mg which can be used as an indicator of the pres ence of the smectite. Information on the Y(III) binding mode with the smectite can be derived from the variation of the Mg:Y ratio as a func tion of the size (Bouby et al, 2011(Bouby et al, , 2012(Bouby et al, , 2015Finck et al, 2012). For Y structurally incorporated within the hectorite structure, the Mg:Y ratio is expected to be constant for all particle sizes.…”
Section: Asymmetrical Flow Field Flow Fractionation (Asflfff)mentioning
confidence: 99%
“…For Y structurally incorporated within the hectorite structure, the Mg:Y ratio is expected to be constant for all particle sizes. For Y(III) adsorbed at the surface of hectorite, the NP associated amount of Y(III) is expected to follow the surface area to volume ratio, and thus the Mg:Y ratio is ex pected to change with the NP size (Bouby et al, 2015).…”
Section: Asymmetrical Flow Field Flow Fractionation (Asflfff)mentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage, it thus can only be concluded that a minor but significant fraction of lutetium present is intimately associated with the detected iron colloids. Due to the irregular shape of the iron colloids (elongated needles on rhombohedra), results might better suggest a lutetium immobilization by incorporation within iron colloids rather than by surface adsorption which might have resulted in a less constant Fe/Lu ratio according to previous studies (Bouby et al 2015;Finck et al 2012). Information on the nature of the Lu species and on the phase(s) immobilizing Lu(III) will be obtained by probing the Lu L 3 -edge by X-ray absorption spectroscopy (see below).…”
Section: Asflfff Combined With Uv-visible Lls and Icp-ms Detectionsmentioning
confidence: 82%
“…The morphology and mineralogical composition of the transformation products, and the Lu(III) repartition between the solid and the liquid phase were determined. Information on the Lu(III) association mode with the particles was obtained by application of the asymmetrical flow field-flow fractionation (AsFlFFF) technique coupled to sensitive detection techniques using similar methodology as in earlier works with various NPs (e.g., (Bouby et al 2011;Bouby et al 2012;Bouby et al 2015;Huber et al 2012)) whereby Fe was used as fingerprint of the presence of Fe phases (hematite and/or goethite). Information on the retention mode and on the nature of the host phase was obtained by X-ray absorption spectroscopy at the Lu L 3 -edge.…”
Section: Introductionmentioning
confidence: 99%